Analisis Proses Rekrutmen Dan Seleksi Terhadap Kinerja Karyawan Rumah Sakit Wijayakusuma Kebumen - Mai Satriyani; Hanung Eka Atmaja (Jurnal Ekonomi dan Bisnis (EK dan BI), 2021)
The performance of human resources in a company is directly proportional to the progress of the company. However, the reality is that there are still organizations that have not been able to achieve maximum organizational goals. Because of this, it is necessary to analyze the recruitment and selection process on employee performance. The existence of a good recruitment and selection process is able to support the acquisition of human resources who have good performance and quality. The purpose of this study was to find out how the recruitment and selection process influences the performance of the Wijayakusuma Hospital employees. In conducting the research, the writer uses descriptive-qualitative research with purposive sampling. The results showed that the recruitment process and selection process had an effect on the performance of Wijayakusuma Hospital employees. In conducting the recruitment process, applicants are limited and prioritized for those who are domiciled in Kebumen, this has an unfavorable impact on employee performance. In the selection of interview tests, there is no patent standard and coordination regarding the stages and assessments in the selection so that it can reduce the objectivity of the assessment in the interview test and get less accurate results.